Implications of Sharia Insurance Bankruptcy on Policyholder Legal Protection (Juridical Analysis of Supreme Court Decision Number 1016/Pdt.Sus-Pailit/2016) - Setyawati, Afifah Yuli; Isman, I (Universitas Muhammadiyah Surakarta, 2023)
Purpose: This article aims to analyse the bankruptcy of PT Asuransi Syariah Mubarakah by describing the profound legal implications for the regulation and protection of policyholders. It outlines the basic concepts of insolvency, the role of the courts, the conditions of insolvency and the legal consequences of bankruptcy status. The article combines bankruptcy law, the assessment of facts in court and the legal consequences of bankruptcy status in a comprehensive analytical framework. Methodology: The method of discussion of this research includes legal review, doctrinal legal analysis, review of judges' considerations (ratio decidendi) related to bankruptcy regulations. The results of the analysis of the judge's considerations study will be used as a basis for understanding the impact of the bankruptcy of Sharia insurance companies on the protection of consumers (policyholders), so that the conclusion of the research can provide a comprehensive and in-depth picture of the legal consequences and implications and projections of the bankruptcy of Sharia insurance companies on the losses of policyholders.. Applications/Originality/Value: The Shari'ah Insurance Bankruptcy Study concluded that financial management, solvency and consumer protection are three legal values that must be maintained not only for the survival of an insurance company, but also because of its systemic impact on policyholders. The application of Shari'ah principles in the management of insurance companies indicates improved consumer protection regulations and the company's responsibility towards its policyholders. The legal protection of policyholders is closely linked to three key concepts: compliance, policyholder confidence and consumer redress.